ANALISIS PEMILIHAN WAREHOUSE UNTUK AIRCRAFT ON GROUND DAN RUSH ORDER CASE DENGAN MENGGUNAKAN METODE ANALYTICAL HIERARCHY PROCESS. (STUDI KASUS: PT. BATAM AERO TEKNIK) - Mukhammad Yusuf Hakim; Abubakar As’siddiq; Rafli Junaidi (Program Studi Teknik Industri Universitas Muhammadiyah Tangerang, 2026)
Lion Group is one of the largest airlines in Southeast Asia and even in the world. Lion Air Group itself has six airlines, including Lion Air Indonesia, Lion Air Thailand, Batik Air Indonesia, Batik Air Malaysia, Super Air Jet, and Wings Air. With such a large fleet, Lion Air Group must also maintain its aircraft to ensure they are airworthy and can support its operations. Approximately 360-400 aircraft undergo routine maintenance, both scheduled and unscheduled. For unscheduled maintenance, Lion Group faces challenges related to the delivery and storage of spare parts, especially for aircraft categorized as AOG (Aircraft On Ground), where the handling process requires high speed and accuracy to meet safety standards and provide passenger service within a short timeframe. Warehouses for AOG spare parts are very limited and are still mixed with general warehouses. Considering that the criteria for warehouses in the aircraft maintenance process are quite strict, a special study is needed to determine them.